Transformasi Digital Pengelolaan Infrastruktur Wilayah oleh PUPR SVJJ Palembang melalui Teknologi Informasi - Iwandri, Mickpri Aditya Setiawan; Reni Septiyanti (Prodi Teknologi Informasi Universitas Muhammadiyah Muara Bungo, 2025)
Road and bridge infrastructure plays a crucial role in supporting mobility and economic growth, particularly in Palembang and its surrounding areas. Effective infrastructure management requires accurate data and integrated systems. The Ministry of Public Works and Housing (PUPR), through the Regional Construction Services Center II Palembang, has implemented the Road and Bridge Data Validation System (SVJJ) to improve efficiency, accuracy, and transparency in infrastructure data and project management. This study aims to evaluate the role and implementation of the SVJJ system in supporting digital transformation within PUPR, identify existing challenges, and provide recommendations for improvement. A descriptive qualitative approach was used, involving literature review, field observations, interviews, and secondary data analysis. The findings show that digital systems—such as digital project management tools and real-time infrastructure monitoring—have enhanced responsiveness, transparency, and reduced project costs and completion times. However, challenges remain, including limited technological infrastructure, suboptimal data integration, and inadequate human resource capacity. Therefore, improving human resource skills, strengthening stakeholder collaboration, and standardizing data formats are essential steps toward optimizing future infrastructure management. This research is expected to serve as input for the development of more effective and sustainable infrastructure policies and strategies.